Queer Sociality After the Antisocial Thesis. (20th September 2018) - Kahan, Benjamin
Abstract: This essay-review maps the central contours and critiques of what is known in US-based sexuality studies as "the antisocial thesis." This thesis, broadly construed, argues that all social life and sociality—encompassing the good life, happiness, and citizenship—is organized by heterosexuality and reproductive futurism (emblematized by the figure of the child) and constitutively excludes queerness. I argue that two recent books, Samuel Steward and the Pursuit of the Erotic: Sexuality, Literature, Archives (2017) and Prince of Tricksters: The Incredible True Story of Netley Lucas, Gentleman Crook (2016) provide new strategies to pursue or ways forward in relation to the antisocial thesis's account of the social.